IMPLEMENTASI INTRUKSI PRESIDEN (INPRES) NO 07 TAHUN 2014 TENTANG KEBIJAKAN KARTU INDONESIA PINTAR (KIP) DALAM MENINGKATKAN MUTU PENDIDIKAN MASYARAKAT MISKIN DI INDONESIA - Asmawati Asmawati (STIA SATYA NEGARA PALEMBANG, 2022)
The Smart Indonesia Card Policy is a government program launched to address the problem that occurs because there are still many students who drop out of school. The Indonesia Smart Card is urgently needed by students who come from underprivileged families who are very vulnerable to dropping out of school. The method used is qualitative method. Data collected through observation, interviews, and documentation. Data analysis techniques are carried out by reducing data, presenting data and drawing conclusions. The quality of education in Indonesia has not gone well. This can be seen from the lack of proper targeting and mistargeting of students who belong to families who are said to be able to still get this assistance, while students who belong to disadvantaged families still cannot experience this Assistance Program. Keywords: Implementation, Smart Indonesia Card (Kip)